STUDI ATAS PELAKSANAAN METODE PBL DAN KONVENSIONAL DALAM HUBUNGANNYA DENGAN PENINGKATAN PRESTASI DAN SOFTSKILL MAHASISWA JURUSAN AKUNTANSI FAKULTAS EKONOMI UNIVERSITAS TRISAKTI - Wibowo Wibowo; Apriani Widya Putri (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2011)
This study aims to examine the relationship between increased student achievement and softskill with student assessment of quality of learning climate, trigger problems and facilitators in the classroom who implement PBL method and conventional method. In addition, this study also aims to compare increased student achievement and sofiskill between class that implement the PBL method and class that implement conventional method. The results of this study show that the classes that implement PBL method, the quality of learning climate has no positive relationship, while trigger quality problems and the facilitator had a positive relationship to increasing student achievement and sofiskill. In the class that implement conventional method, the quality of learning climate and trigger the problem does not have a positive relationship, while the quality of the facilitators have a positive relationship to increasing student achievement and sofiskill. In addition, there are also differences between the increase in student achievement and sofiskill in the class that implement the PBL method and class that implement conventional method.